Analisis Makanan Tinggi Natrium terhadap Kejadian Hipertensi pada Pra Lansia dan Lansia di Puskesmas Medan Area Selatan - Diba, Farah; Haningsih, Sri; Pangestuti, Dewi; Nasution, Halimah Thania (Universitas HKBP Nommensen, 2023)
Background: The older a person is, the more susceptible they are to many diseases, especially the elderly. Unhealthy diet and lifestyle can affect the immune system of the elderly, making them more susceptible to various diseases, one of which is hypertension. The number of people with hypertension and the death rate due to hypertension and its complications is increasing every year.Objective: To analyze the consumption of high-sodium foods on the incidence of hypertension in the elderly at the Medan Area South Health Center.Methods: This research is an analytic research with a cross sectional approach. This research was conducted at the Medan Health Center in the South area in November 2022–March 2023. The sample in this study were elderly people who suffered from hypertension with a total sample of 68 people. Data taken through a questionnaire is primary data and analyzed univariately and bivariately using the Somers'd test.Results: The characteristics of the respondents in this study were found to be more female (54.4%), aged between 45-59 years (54.4%), and worked with a predominance of self-employed jobs (39.7%). The pattern of sodium intake in this study was more in the high sodium intake category (55.9%). The blood pressure category of respondents in this study had more hypertension grade 1 blood pressure (51.5%). Based on the bivariate test, it was found that more respondents had a high sodium intake category with hypertension degree 1 blood pressure.Conclusion: Based on the Somers' D analysis test, a significant relationship was found between consumption of high-sodium foods and the incidence of hypertension in the elderly at the Medan Area South Health Center (p value 0.000).Keywords: Hypertension, Consumption, Elderly, Sodium